Paulo Freire: Some Reflections - Peerzada, Najmah (JOURNAL OF INDIAN EDUCATION, 2010)
Paulo Freire had contributed a philosophy of education that came not only from the classical approaches stemming from Plato but also from the modern Marxist and anti-colonialist thinkers. The article briefly summarises the biography of the Paulo, his thoughts, specially his writings on the Pedagogy of the Oppressed which he dedicated to the oppressed and to those who suffer with them and fight at their side. Freire includes a detailed Marxist class analysis in his exploration of the relationship between the coloniser and the colonised. Freire is also known for attack on what he called the banking concept of education in which the student was viewed as an empty account to be filled by the teacher.